Nonlinear optical CLBO crystal anti-reflection moisture-proof protective film and preparation method thereof
By coating and heat-treating the HfO2/SiO2 film layer on the surface of the CLBO crystal, the problem of CLBO crystal being prone to delivery in room temperature and atmospheric environment is solved, and long-term use and high laser performance are achieved in ordinary atmospheric environments.
Patent Information
- Application Number
- CN202411902345.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-23
AI Technical Summary
CLBO crystals are prone to dehydration in room temperature and atmospheric environments. In the prior art, the use of thermal field isolation water vapor technology requires continuous heating, which is inconvenient to use and high energy consumption, and cannot improve transmittance and affect optical quality.
The HfO2/SiO2 film layer was prepared by sol-gel method, and uniformly coated on the surface of CLBO crystals by lifting method, and heat treatment was performed to form a dense protective film layer to isolate the contact between water molecules in the air and crystals.
In ordinary atmospheric environments, effectively prevent the deliques of CLBO crystals, increase the transmittance of crystal elements, reduce laser losses, and improve the laser performance of the crystal.
Smart Images

Figure CN119667828A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical films, and in particular to a nonlinear optical CLBO crystal anti-reflection moisture-proof protective film and a preparation method thereof. Background Art
[0002] Cesium lithium borate (CsLiB6O 10 , referred to as CLBO) crystal is a very important new type of nonlinear optical crystal with a light transmission range of 180-2750nm. It can be used for neodymium laser quadruple frequency (FHG) to obtain 266nm, quintuple frequency (5HG) to obtain 213nm and difference frequency (SFG) to obtain 193nm vacuum ultraviolet wavelength. The crystal has a high laser damage threshold, a small walk-off angle, a large acceptable angle, a large temperature bandwidth and a large spectral bandwidth, especially in the field of high-power ultraviolet and deep ultraviolet solid lasers. It has a broad application prospect.
[0003] CLBO crystals have excellent ultraviolet nonlinear properties, but CLBO crystals will absorb water molecules in the air and deliquesce and crack under room temperature atmospheric environment, which restricts the promotion and application of CLBO crystals. Foreign researchers have proposed a method to solve the deliquesce of CLBO crystals - thermal field isolation water vapor technology, which places the CLBO crystal element in a temperature-controlled moisture-proof box at a temperature of about 100-160°C. The use of a temperature-controlled box for moisture-proofing requires continuous and uninterrupted heating and protection of the crystal device to isolate water molecules from contacting the CLBO crystal element. It is inconvenient to use and has high energy consumption. It is subject to many restrictions such as power supply, structural weight, and application environment. It cannot improve the transmittance of the CLBO element, and repeated heating and cooling during use also have a certain impact on the optical quality of the crystal.
[0004] Chinese invention patent CN103757706A discloses a method for preparing an anti-reflection protective film on the surface of a nonlinear optical crystal. For deliquescent nonlinear optical crystals, a method for preparing a moisture-proof + anti-reflection double-layer anti-reflection protective film is provided based on the sol properties and film layer structure. However, the preparation method is cumbersome and requires a two-step method: that is, a modified anti-reflection film is coated on the crystal coated with a moisture-proof film. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a dense nonlinear optical CLBO crystal anti-reflection moisture-proof protective film with high resistance to laser damage, which is used to significantly extend the service life of crystal elements and improve the laser performance of crystals.
[0006] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:
[0007] On the one hand, a method for preparing a nonlinear optical CLBO crystal anti-reflection and moisture-proof protective film is provided, which includes the following steps: using a sol-gel method to prepare a high-refractive index HfO2 film and a low-refractive index SiO2 film layer, and matching them and heat treating them to make an anti-reflection and moisture-proof protective film for the CLBO crystal.
[0008] Furthermore, the organic alkoxide hafnium n-propoxide is used as a precursor to prepare a high refractive index HfO2 film.
[0009] Furthermore, a low refractive index SiO2 film layer is prepared using tetraethyl orthosilicate.
[0010] Furthermore, the preparation method of hafnium n-propoxide sol specifically comprises the following steps:
[0011] Acetylacetone with a purity of 99.9% or more is dissolved in anhydrous ethanol to prepare a solution A with a mass concentration of 5 to 20 wt %; hafnium n-propoxide with a purity of 99.9% or more is dissolved in anhydrous ethanol to prepare a solution B with a mass concentration of 5 to 20 wt %;
[0012] Under vigorous stirring, solution A is added dropwise into solution B, and then hydrochloric acid with a mass concentration of 0.1-0.2wt% is added to adjust the pH to 3-5. At 40-60°C, stirring is carried out for 1-5 hours to obtain a hafnium n-propoxide sol with a mass concentration of 3-8wt%.
[0013] Furthermore, the preparation method of tetraethyl orthosilicate sol specifically comprises the following steps:
[0014] Dissolve ethyl orthosilicate with a purity of 99.9% or more in anhydrous ethanol to prepare a solution C with a mass concentration of 3 to 20wt%, then add hydrochloric acid with a mass concentration of 0.1 to 0.2wt%, adjust the pH to 2 to 5, stir for 8 to 24 hours at 50 to 80°C, and obtain a ethyl orthosilicate sol with a mass concentration of 2 to 9wt%.
[0015] Furthermore, the hafnium n-propoxide sol:ethyl orthosilicate sol is uniformly coated on the surface of the CLBO crystal by a Czochralski method in a ratio of 3-7 wt %.
[0016] Furthermore, the CLBO crystal coated with the anti-reflection and moisture-proof protective film is heat-treated at 150-200° C. for 4-10 hours to form a dense HfO2 / SiO2 protective film layer.
[0017] Another invention provides a nonlinear optical CLBO crystal anti-reflection moisture-proof protective film, which is a HfO2 / SiO2 deep ultraviolet anti-reflection moisture-proof protective film.
[0018] The beneficial effects of the present invention are:
[0019] The present invention adopts the sol-gel pulling method to coat the HfO2 / SiO2 deep ultraviolet anti-reflection moisture-proof protective film, and the preparation method is simple, that is, the sol-gel method is used to prepare the HfO2 film with a higher refractive index and laser damage threshold, and the anti-reflection film is matched with the low refractive index SiO2 film layer. It can isolate the water molecules in the air from contacting the crystal, avoid the erosion of the crystal by the water molecules and the occurrence of deliquescence reaction, and at the same time increase the transmittance of the crystal element, greatly reduce the laser loss, and improve the laser performance of the crystal. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The transmittance comparison at 210nm of CLBO crystal and after coating is measured in Example 3 and Example 4;
[0021] Figure 2 The transmittance comparison at 263nm of CLBO crystal and after coating is measured in Example 3 and Example 4;
[0022] Figure 3 The transmittance comparison at 1053nm of CLBO crystal and after coating is measured in Example 3 and Example 4;
[0023] Figure 4 This is the CLBO crystal coated with the HfO2 / SiO2 protective film in Example 3 and Example 4 after being placed in a normal atmospheric environment for 4 months. DETAILED DESCRIPTION
[0024] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0025] Example 1
[0026] Acetylacetone with a purity of 99.9% is dissolved in anhydrous ethanol (superior grade) to prepare a solution A with a mass concentration of 5wt%; hafnium n-propoxide with a purity of 99.9% is dissolved in anhydrous ethanol (superior grade) to prepare a solution B with a mass concentration of 10wt%; solution A is added dropwise into solution B, and then hydrochloric acid with a mass concentration of 0.1wt% is added to adjust the pH to 3, and the mixture is stirred at 40°C for 4 hours to obtain a hafnium n-propoxide sol with a mass concentration of 4wt%.
[0027] Ethyl orthosilicate with a purity of 99.9% was dissolved in anhydrous ethanol (super pure) to prepare a solution C with a mass concentration of 5wt%, and then hydrochloric acid with a mass concentration of 0.15wt% was added to adjust the pH to 2. The mixture was stirred at 50°C for 8 hours to obtain a 3wt% ethyl orthosilicate sol.
[0028] The synthesized hafnium n-propoxide sol and tetraethyl orthosilicate sol are uniformly coated on the surface of the CLBO crystal to be protected by a Czochralski method in a ratio of 3 wt % of hafnium n-propoxide sol and tetraethyl orthosilicate sol to form an anti-reflection and moisture-proof protective film.
[0029] The CLBO crystal coated with an anti-reflection and moisture-proof protective film was heat-treated at 150°C for 8 hours to form a dense HfO2 / SiO2 protective film layer.
[0030] Water was dripped onto the CLBO crystal coated with HfO2 / SiO2 protective film with a pipette and left for 4 hours. No deliquescence of the crystal was observed.
[0031] Example 2
[0032] Acetylacetone with a purity of 99.9% is dissolved in anhydrous ethanol (superior grade) to prepare a solution A with a mass concentration of 10wt%; hafnium n-propoxide with a purity of 99.9% is dissolved in anhydrous ethanol (superior grade) to prepare a solution B with a mass concentration of 10wt%; solution A is added dropwise into solution B, and then hydrochloric acid with a mass concentration of 0.2wt% is added, the pH is adjusted to 5, and the mixture is stirred at 60°C for 2 hours to obtain a hafnium n-propoxide sol with a mass concentration of 3wt%.
[0033] Ethyl orthosilicate with a purity of 99.9% was dissolved in anhydrous ethanol (super pure) to prepare a solution C with a mass concentration of 15wt%, and then hydrochloric acid with a mass concentration of 0.15wt% was added to adjust the pH to 3. The mixture was stirred at 80°C for 12 hours to obtain a 6wt% ethyl orthosilicate sol.
[0034] The synthesized hafnium n-propoxide sol and tetraethyl orthosilicate sol are uniformly coated on the surface of the CLBO crystal to be protected by a Czochralski method in a ratio of 5wt% of hafnium n-propoxide sol:tetraethyl orthosilicate sol to form an anti-reflection and moisture-proof protective film.
[0035] The CLBO crystal coated with an anti-reflection and moisture-proof protective film was heat-treated at 200°C for 4 hours to form a dense HfO2 / SiO2 protective film layer.
[0036] The CLBO crystal coated with HfO2 / SiO2 protective film was placed in a constant temperature and humidity chamber at 25°C and 90% relative humidity, and no deliquescence was observed for 2 months.
[0037] Example 3
[0038] Acetylacetone with a purity of 99.9% is dissolved in anhydrous ethanol (superior grade) to prepare a solution A with a mass concentration of 20wt%; hafnium n-propoxide with a purity of 99.9% is dissolved in anhydrous ethanol (superior grade) to prepare a solution B with a mass concentration of 15wt%; under the condition of vigorous stirring, solution A is added dropwise into solution B, and then hydrochloric acid with a mass concentration of 0.2wt% is added to adjust the pH to 5, and stirring is carried out at 60°C for 5 hours to obtain a hafnium n-propoxide sol with a mass concentration of 8wt%.
[0039] Ethyl orthosilicate with a purity of 99.9% was dissolved in anhydrous ethanol (super pure) to prepare a solution C with a mass concentration of 20wt%, and then hydrochloric acid with a mass concentration of 0.2wt% was added to adjust the pH to 5. The mixture was stirred at 80°C for 24 hours to obtain a 9wt% ethyl orthosilicate sol.
[0040] The synthesized hafnium n-propoxide sol and tetraethyl orthosilicate sol are uniformly coated on the surface of the CLBO crystal to be protected by a Czochralski method in a ratio of 7 wt % of hafnium n-propoxide sol and tetraethyl orthosilicate sol to form an anti-reflection and moisture-proof protective film.
[0041] The CLBO crystal coated with an anti-reflection and moisture-proof protective film was heat-treated at 200°C for 8 hours to form a dense HfO2 / SiO2 protective film layer.
[0042] When the CLBO crystal coated with HfO2 / SiO2 protective film was placed in a normal atmospheric environment, no deliquescence was observed for 4 months, and the transmittance of the crystal element at 210nm, 263nm, and 1053nm increased by 4.29%, 7.08%, and 2.19%, respectively, indicating that the HfO2 / SiO2 film can isolate water molecules in the air from contacting the crystal and prevent deliquescence. At the same time, it can increase the transmittance, reduce laser loss, and improve the crystal's quadrupled and quintupled laser performance.
[0043] Example 4
[0044] Acetylacetone with a purity of 99.9% is dissolved in anhydrous ethanol (superior grade) to prepare a solution A with a mass concentration of 15wt%; hafnium n-propoxide with a purity of 99.9% is dissolved in anhydrous ethanol (superior grade) to prepare a solution B with a mass concentration of 20wt%; under the condition of vigorous stirring, solution A is added dropwise into solution B, and then hydrochloric acid with a mass concentration of 0.2wt% is added to adjust the pH to 3, and stirring is carried out at 50°C for 5 hours to obtain a hafnium n-propoxide sol with a mass concentration of 3wt%.
[0045] Dissolve ethyl orthosilicate with a purity of 99.9% in anhydrous ethanol (superior grade) to prepare a solution C with a mass concentration of 10wt%, then add hydrochloric acid with a mass concentration of 0.2wt%, adjust the pH to 4, stir at 80°C for 24 hours, and obtain a ethyl orthosilicate sol with a mass concentration of 7.5wt%.
[0046] The synthesized hafnium n-propoxide sol and tetraethyl orthosilicate sol are uniformly coated on the surface of the CLBO crystal that needs protection by using a Czochralski method in a ratio of 6 wt % of hafnium n-propoxide sol and tetraethyl orthosilicate sol to form an anti-reflection and moisture-proof protective film.
[0047] The CLBO crystal coated with an anti-reflection and moisture-proof protective film was heat-treated at 160°C for 10 hours to form a dense HfO2 / SiO2 protective film layer.
[0048] When the CLBO crystal coated with HfO2 / SiO2 protective film was placed in a normal atmospheric environment, no deliquescence was observed for 4 months, and the transmittance of the crystal element at 210nm, 263nm, and 1053nm increased by 4.31%, 7.07%, and 2.18%, respectively, indicating that the HfO2 / SiO2 film can isolate water molecules in the air from contacting the crystal and prevent deliquescence. At the same time, it can increase the transmittance, reduce laser loss, and improve the crystal's quadrupled and quintupled laser performance.
[0049] In summary, the present invention proposes coating the HfO2 / SiO2 anti-reflection and moisture-proof protective film on the light-transmitting surface and the non-light-transmitting surface of the CLBO crystal, which can isolate the water molecules in the air from contacting the crystal in a normal atmospheric environment, avoid the crystal from deliquescing and cracking, and lose the nonlinear optical frequency conversion function of the crystal. The crystal can be stored and used normally in a normal atmospheric environment, while increasing the transmittance of the crystal (see Figure 1-3 , Table 1), improving the performance of crystal lasers, and has broad application prospects in high-power ultraviolet and deep ultraviolet laser technologies.
[0050] Table 1 Comparison of measured transmittance of CLBO crystal and after coating
[0051] Wavelength (nm) 210 263 1053 Crystal transmittance (%) 88.12 91.54 93.56 Transmittance of coated crystal element (%) 92.43 98.61 95.84 Transmittance increase (%) 4.31 7.07 2.28
[0052] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0053] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a nonlinear optical CLBO crystal anti-reflection moisture-proof protective film, characterized in that: The following steps are involved: A high refractive index HfO2 film and a low refractive index SiO2 film were prepared by the sol-gel method, and then matched and heat-treated to form an anti-reflection and moisture-proof protective film for CLBO crystal.
2. The method for preparing the nonlinear optical CLBO crystal anti-reflection moisture-proof protective film according to claim 1, characterized in that: High refractive index HfO2 film was prepared using organic alkoxide hafnium n-propoxide as precursor.
3. The method for preparing the nonlinear optical CLBO crystal anti-reflection moisture-proof protective film according to claim 2, characterized in that: The low refractive index SiO2 film layer was prepared using tetraethyl orthosilicate.
4. The method for preparing the nonlinear optical CLBO crystal anti-reflection moisture-proof protective film according to claim 2, characterized in that: The preparation method of hafnium n-propoxide sol specifically comprises the following steps: Acetylacetone with a purity of 99.9% or more is dissolved in anhydrous ethanol to prepare a solution A with a mass concentration of 5 to 20 wt %; hafnium n-propoxide with a purity of 99.9% or more is dissolved in anhydrous ethanol to prepare a solution B with a mass concentration of 5 to 20 wt %; Under vigorous stirring, solution A is added dropwise into solution B, and then hydrochloric acid with a mass concentration of 0.1-0.2wt% is added to adjust the pH to 3-5. At 40-60°C, stirring is carried out for 1-5 hours to obtain a hafnium n-propoxide sol with a mass concentration of 3-8wt%.
5. The method for preparing the nonlinear optical CLBO crystal anti-reflection moisture-proof protective film according to claim 3, characterized in that: The preparation method of tetraethyl orthosilicate sol specifically comprises the following steps: Ethyl orthosilicate with a purity of 99.9% or more is dissolved in anhydrous ethanol to prepare a solution C with a mass concentration of 3 to 20wt%, and then hydrochloric acid with a mass concentration of 0.1 to 0.2wt% is added to adjust the pH to 2 to 5, and stirred at 50 to 80°C for 8 to 24 hours to obtain an ethyl orthosilicate sol with a mass concentration of 2 to 9wt%.
6. The method for preparing the nonlinear optical CLBO crystal anti-reflection moisture-proof protective film according to claim 3, characterized in that: The hafnium n-propoxide sol:ethyl orthosilicate sol is uniformly coated on the surface of the CLBO crystal by a pulling method according to a ratio of 3-7 wt %.
7. The method for preparing the nonlinear optical CLBO crystal anti-reflection moisture-proof protective film according to claim 1, characterized in that: The CLBO crystal coated with an anti-reflection and moisture-proof protective film is subjected to a heat treatment at 150-200° C. for 4-10 hours to form a dense HfO2 / SiO2 protective film layer.
8. A nonlinear optical CLBO crystal anti-reflection moisture-proof protective film prepared by the method according to any one of claims 1 to 7, characterized in that: It is a HfO2 / SiO2 deep ultraviolet anti-reflection moisture-proof protective film.
Citation Information
Patent Citations
Method for preparing organic silicon dampproof protection film on surface of borate crystal
CN101565856A
Holographic grating manufactured by HfO2 / SiO2 sol-gel glass
CN102243327A
Preparation method of nonlinear optical crystal surface antireflection protective film
CN103757706A
Preparation method of lithium triborate crystal high-laser-damaged-threshold antireflection film
CN106435487A
Method for preparing ZrO2-SiO2 binary mixed sol coating by adopting sol-gel method
CN112759388A